The Narrating Ontology Morality of Corruption Law in Indonesia Based on Islamic Value - Sidik Sunaryo; Shinta Ayu Purnamawati; Muhammad Jihadi; Sholahuddin Al-Fatih (Unissula, 2025)
This article aimed to explain the ontology morality of corruption law in Indonesia from an Islamic value. The meaning of justice in the study of law contains the value of goodness and truth. The value of goodness has a home in the realm of 'taste,' which provides a foundation and direction towards the spirit of conscience. Philosophically, it must be done fundamentally, deeply, and thoroughly to the meanings of god's attributes in essence (ontology). The philosophical approach is one of the options for this article, besides the concept approach and doctrine (epistemology). Although realized, there is a firm limit to rational ability in providing the meanings of justice, certainty, and usefulness of the law. Limited ability shows 'dwarfity' and rational superiority under 'breadth' divine values and attributes. The ontology of legal morality in a country can be explored from its ideology, which is the source of basic values that guide the direction of the purpose of the establishment of a country. The constitution became a method to justify the realization of one's country's purpose. State ideology became the rail of formation, change, revocation, and enforcement of its laws. As a result, the goal of this analysis is to show how these religious beliefs strengthen legal frameworks, ensuring that corruption is viewed not only as a legal infringement but also as a serious moral breach that undermines society's well-being. To summarize, integrating Islamic moral concepts with corruption law increases the ethical foundations of legal systems, fostering both legal deterrence and moral accountability in governance.